Re-tooling Human Resource Management. A critical analysis of chances, risks and barriers of People Analytics in Human Resource Management - Katja Biermann (2019)
Growing availability of data and exploitation of new data sources have transformed not only private life but also increasingly shape business functions. In the light of rising global competitive pressure, Human Resource Management has now begun to embrace the potential of utilizing data in form of People Analytics to overcome strategic deficits. Based on an extensive literature review the purpose of this thesis is to critically analyze postulated chances of People Analytics for Human Resource Management as well as outlining possible risks and potential implementation barriers. Findings indicate that despite clear chances for Human Resource Management, severe barriers are causing a current infancy stage of People Analytics in companies. Main implementation barriers identified are a lack of data quality, access and analytical skills, privacy issues, implementation costs, a lack of leadership commitment and cultural change readiness. To what extent the People Analytics hype will develop into management reality and lead the strategic transformation of HRM will therefore depend on whether companies are able to counter outlined barriers with effective strategies.